Impact of Agency Costs on Firm Performance: Evidence from Vietnam - Hoang, Le Duc; Tuan, Tran Minh; Nha, Pham Van Tue; Nha, Pham Van Tue; Phuong, Ta Thu (Organizations and Markets in Emerging Economies, 2019)
An assumption in agency costs theory is that agency costs can exert a negative impact on firm performance. In this study, we examine the impact of agency costs on firm performance of Vietnamese listed companies. Our sample includes 736 companies in Vietnam during the period om 2010 to 2015. We find that agency costs exert a negative impact on firm performance. Our results are robust to alternative econometric models, including an instrumental variables technique and a system generalized method of moment model. In addition, we show that a debt instrument can be a useful tool to reduce the negative impact of agency costs on firm performance.